Fast recovery of ion-irradiation-induced defects in Ge2Sb2Te5 thin films at room temperature - Hafermann, Martin; Schock, Robin; Wan, Chenghao; Rensberg, Jura; Kats, Mikhail A.; Ronning, Carsten (Optical Materials Express, 2021)
Phase-change materials serve a broad field of applications ranging from non-volatile electronic memory to optical data storage by providing reversible, repeatable, and rapid switching between amorphous and crystalline states accompanied by large changes in the electrical and optical properties. Here, we demonstrate how ion irradiation can be used to tailor disorder in initially crystalline Ge2Sb2Te5 (GST) thin films via the intentional creation of lattice defects. We found that continuous Ar+-ion irradiation at room temperature of GST films causes complete amorphization of GST when exceeding 0.6 (for rock-salt GST) and 3 (for hexagonal GST) displacements per atom (ndpa). While the transition from rock-salt to amorphous GST is caused by progressive amorphization via the accumulation of lattice defects, several transitions occur in hexagonal GST upon ion irradiation. In hexagonal GST, the creation of point defects and small defect clusters leads to the disordering of intrinsic vacancy layers (van der Waals gaps) that drives the electronic metal–insulator transition. Increasing disorder then induces a structural transition from hexagonal to rock-salt and then leads to amorphization. Furthermore, we observed different annealing behavior of defects for rock-salt and hexagonal GST. The higher amorphization threshold in hexagonal GST compared to rock-salt GST is caused by an increased defect-annealing rate, i.e., a higher resistance against ion-beam-induced disorder. Moreover, we observed that the recovery of defects in GST is on the time scale of seconds or less at room temperature.
CRIS-Team Scopus Importer:2023-04-20